PENGATURAN KERJASAMA ANTARA GOOGLE ADSENSE DENGAN YOUTUBER KOTA MEDAN PERSPEKTIF WAHBAH ZUHAILI - Alfi Karomah (ISLAMIC BUSSINESS LAW REVIEW, 2019)
This thesis is entitled: "Collaborative Arrangements Between Google Adsense and Youuber Medan City Perspective Wahbah Zuhaili". The problem in this research is the regulation of cooperation between Google Adsense and YouTube, is it already in conformity with and does not violate the Shari'a and the applicable law in Indonesia. This research was conducted in Medan City. This research is a joint research between field research and library research. In this research the method used is interviews and data obtained in content uploaded by YouTube on his channel. The conclusion of this thesis is the Arrangement of Collaboration between Google Adsense and the Medan City Youtuber Wahuh Zuhaili's perspective. So the results of the author's research on the cooperation of Google Adsense with Youtuber based on Wahbah Az-Zuhaili's perspective is Haram if it does not follow the pillars and syirkah conditions and the applicable laws in Indonesia. The status can change if, the Youtubers meet the requirements and get along well, and follow all the rules permitted by the Shariah 'and the Law. Because according to Wahbah Zuhaili "There are no legal and legal forms of business except if permitted by sharia, and no form of business that is not clear (vague) and can destroy the relationship of affection and cooperation between humans unless shariah is forbidden and the door is closed. And set in the Civil Code article 1320 for the validity of the agreement required four conditions, their agreement to bind themselves, the ability to make an agreement, a certain thing, a halal cause.